The value of relational learning in global buyer‐supplier exchanges: a dyadic perspective and test of the pie‐sharing premise - Cheung, Mee‐Shew; Myers, Matthew B.; Mentzer, John T. (Strategic Management Journal, 2011)
Research in collaborative interorganizational relationships has typically focused on the value of these relationships to a specific supply chain partner. Furthermore, the phenomenon has rarely been explored in a global setting. Using primary data from 126 cross‐border dyads, we investigate the influence of relational learning on the relationship performance of both the buyer and the supplier, testing the contention that both members (1) benefit from relational learning efforts and (2) enjoy equal pieces of the benefits pie. We find that three specific types of relational learning (information sharing, joint sensemaking, and knowledge integration) influence relationship performance, and that these dimensions of relational learning affect supply chain partners in different ways. We draw conclusions regarding the relative value of relational learning for both buyers and suppliers. Copyright © 2011 John Wiley & Sons, Ltd.